Experimental study on slope consolidation sand tanks based on the artificial ground freezing method - Wang, Zhenwei; Cao, Huiqing; Wang, Shaoqi; Zhao, Mengfei; Song, Wei (Frontiers in Built Environment, 2025)
Slope stability is an important factor affecting safe production in large surface coal mines. Most traditional slope fixation methods adopt grouting and anchor reinforcement. However, cementing rock and soil using conventional methods is challenging in areas with high water content. This study innovatively proposes the application of artificial ground freezing technology to reinforce the slopes of large-scale open-pit coal mines and verifies the technical feasibility of this technique. Five conditions are investigated via sandbox tests and the development characteristics of the freezing temperature field are analyzed. The results show that different water contents, lithologies, and the presence or absence of seepage affect freezing. Specifically, when the water content is 7.3%, the freezing radius is 220 mm; when the water content is increased to 27.4%, the freezing radius extends to 300 mm. Sand has the fastest freezing rate at 0.072°C/h, while lignite has the slowest freezing rate at 0.061°C/h. The temperature drop rates are 0.068°C and 0.058°C/h for the impermeable and seepage conditions, respectively. Moreover, the fitting function y = A1e-x/A2+A3 adequately describes the temperature profile decrease. The results of the study provide a basis for the precise design of freezing programs to further realize green and low-carbon, large-scale slope stabilization.